Le mouvement de santé en français en contexte linguistique minoritaire : les représentations des acteurs sur l'avenir des services - Bouchard, Louise (Revue canadienne de sociologie, 2011)
Le plan d'action pour les langues officielles lancé en 2003 projette de revitaliser la dualité linguistique du pays. Parmi les domaines prioritaires, la santé se voit privilégier dans le but d'assurer la formation des professionnels de la santé pour desservir les communautés de langue officielle minoritaire et de réseauter les principaux acteurs préoccupés par l'organisation des services dans la langue minoritaire. L'objectif de cet article est de rendre compte des représentations des francophones en situation linguistique minoritaire eu égard à l'avenir des services de santé en français. L'étude repose sur une méthodologie participative: la cartographie conceptuelle permettant de recenser l'univers conceptuel d'une problématique donnée.

Availability, accessibility and acceptability of english-language mental health services for the Estrie region’s english-speaking population: Service user and provider perspectives - Charpentier, Claude; Stout, Dale; Poulin, Edith; Philip, Christopher; Benoit, Annie (Journal of Eastern Townships Studies, 2011)
Mental illness affects about 1 in 5 Canadians during their lifetime but only approximately 30% of people needing help actually access mental health ser vices (Gravel, Connolly & Bédard, 2004). This low access rate is worrisome and may not accurately depict the reality as it is lived out by linguistic minorities. The present study documents both the need for and access to English-lan guage mental health services by the Estrie region’s English-speaking minority. Intending to record their needs and access experiences against the backdrop of available English-language mental health services, both users and providers of these services were surveyed in tandem. This novel approach to mental health needs assessment research shows the precarious situation of this minority community (high need/low access to language-congruent mental health ser vices) to be further compromised by misperceptions of service availability.
Aussi à : https://www.etrc.ca/wp-content/uploads/2016/12/JETS_36-5-Charpentier.pdf

Les défis et les enjeux liés au maintien à domicile des aînés: une étude de cas en milieu urbain néo-brunswickois - Dupuis-Blanchard, Suzanne; Simard, Majella; Gould, Odette; Villalon, Lita (Université de Moncton, 2011)
fs-ref-orig: Dupuis-Blanchard, S., Simard, M., Gould, O. et Villalon, L. (2011). Les défis et les enjeux liés au maintien à domicile des aînés : une étude de cas en milieu urbain néo-brunswickois. Université de Moncton. fs-code-orig: Dupuis-Blanchard-2011

Access to health care services and self-perceived health of canada's official-language minorities [master's thesis, University of Ottawa] - Gagnon-Arpin, Isabelle (University of Ottawa, 2011)
fs-ref-orig: Gagnon-Arpin, I. (2011). Access to health care services and self-perceived health of canada's official-language minorities [master's thesis, University of Ottawa]. uO Research. http://dx.doi.org/10.20381/ruor-4657 fs-code-orig: Gagnon-Arpin-2011c